ANALISIS FREKUENSI SEL PIKNOSIS PADA EPITEL MUKOSA BUKAL PEKERJA DRY CLEANING DI YOGYAKARTA AKIBAT PAPARAN PERCHLOROETHYLENE (PCE) - , INTAN KUMALADEWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dry cleaning is a textile-washing method using special solvent, such as perchloroethylene instead of water. Perchloroethylene (PCE) is suspected to be toxic and has the potential to harm human body. This solvent can enter the human body through inhalation or ingestion. Respiratory tract are connected to oral cavity by pharynx. Pyknosis is the early phase of abnormal cells destruction called necrosis. The aim of this study was to evaluate pyknosis frequency in buccal mucosal epithelial cells of dry cleaning workers who frequently exposed to PCE through inhalation. The subjects of this research were 12 dry cleaning workers of dry cleaning industry in Yogyakarta which had been exposed continuously by PCE for more than 1 years. The subjects for control group were 12 individuals who didnât exposed to PCE. Buccal mucosa cells were swabbed using cytobrush on the left side of buccal mucosa and stained using Feulgen-Rossenbeck modification method. Identification and calculation was conducted under light microscope with 200 magnification. The frequency of pyknosis cells were calculated per 1000 cells. Furthermore, the data were analyzed using independent sample t-test and continued with One-Way Anova test (p<0.05). The result showed that there was a significant difference of pyknosis cells frequency between the dry cleaning workers and the control group. In conclusion, PCE exposure increase the pyknosis cells frequency on buccal mucosa ephitelial cells of dry cleaning workers in Yogyakarta. In addition, the pyknosis cells frequency increase after 7 years exposure.